A finite element analysis to study the stress distribution on distal implants in an all-on-four situation in atrophic maxilla as affected by the tilt of the implants and varying cantilever lengths - Anju Kumari; Puja Malhotra; Shefali Phogat; Bhupender Yadav; Jaiveer Yadav; Sumit Singh Phukela (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this work was to evaluate stress distribution on implants in All-on-Four situation with varying distal implant angulations (30°,40°,45°) and varying cantilever lengths (4 mm, 8 mm, 12 mm, 16 mm) in atrophic maxilla using finite element analysis. Setting and Design: A in vitro study, finite element analysis. Materials and Methodology: Three-dimensional finite element model of an edentulous maxilla restored with a prosthesis supported by four implants was reconstructed to carry out the analysis. Three different configurations, corresponding to 3 tilt degrees of the distal implants (30°, 40°, and 45°) were subjected to 4 loading simulations. Statistical Analysis Used: The results of the simulations obtained were evaluated in terms of Von Mises equivalent stress levels at the bone-implant interface. Result: From a stress-level viewpoint, the 45° model was revealed to be the most critical for peri-implant bone. In all the loading simulations, the maximum stress values were always found at the neck of the distal implants. With increasing distal implant tilt, cantilever length reduces depending on the quality of bone. At 30° angulation of distal implant a maximum cantilever length of 16 mm may be given if the quality of bone is D3 but only 8 mm cantilever may be recommended if bone quality is D4. At 40° angulation, 16 mm in D3 bone and 0 mm in D4 bone whereas at 45° angulation, it reduces to 12 mm in D3 bone and no cantilever is recommended with D4 bone. Conclusion: The 45° tilt induced higher stress values at the bone-implant interface, especially in the distal aspect, than the other 2 tilts analyzed. Stress values increased with increased cantilever length which was further influenced by the distal implant tilt and the quality of the bone.